Assessing the impact of a waiting time survey on reducing waiting times in urban primary care clinics in Cape Town, South Africa - Johann Daniels; Virginia Zweigenthal; Gavin Reagon (AOSIS, 2017)
A waiting time survey (WTS) conducted in several clinics in Cape Town, South Africa provided recommendations on how to shorten waiting times (WT). A follow-up study was conducted to assess whether WT had reduced. Using a stratified sample of 22 clinics, a before and after study design assessed changes in WT. The WT was measured and perceptions of clinic managers were elicited, about the previous survey's recommendations. The overall median WT decreased by 21 minutes (95%CI: 11.77- 30.23), a 28% decrease from the previous WTS. Although no specific factor was associated with decreases in WT, implementation of recommendations to reduce WT was 2.67 times (95%CI: 1.33-5.40) more likely amongst those who received written recommendations and 2.3 times (95%CI: 1.28- 4.19) more likely amongst managers with 5 or more years' experience. The decrease in WT found demonstrates the utility of a WTS in busy urban clinics in developing country contexts. Experienced facility managers who timeously receive customised reports of their clinic's performance are more likely to implement changes that positively impact on reducing WT.